A STUDY ON THE EFFECTIVENESS OF MULTIMEDIA IN TEACHING COMPUTER SCIENCE AMONG XI STANDARD STUDENTS IN KARUR DISTRICT - Subashini, V.K. (International Journal of Research -GRANTHAALAYAH, 2016)
This study attempted to find out the effect of using multimedia in teaching Computer Science among XI students. Sample of 62 students was selected for the study in Karur District. Two groups pretest and posttest experimental design was used. Data were analyzed. It is found that there is a significant means score difference between pretest and posttest among the selected higher secondary school novice students. It is proved that Multimedia supported teaching is one of the appropriate and effective methods for teaching Computer Science to higher secondary school students.